Ecological Assessment of Heavy Metal Concentrations in Fish Species and Aquatic Environments in the Vicinity of the Baropukuria Coal Mine Industry of Bangladesh: A Seasonal Perspective - MD. SHAHANUR ALAM; MD. MASUD RANA; ZANNATUL FERDOUSHI; K.M. TOUFIQ HASSAN (Asian Fisheries Science)
Heavy-metal pollution of surface water, sediment and fish is recognized as a significant global issue, particularly affecting developing countries like Bangladesh. Water quality is drastically diminished due to industrial discharge of heavy metals. The present study aimed to explore different physico-chemical water quality parameters and the level of heavy metal concentration in sediment, water and muscle of fish species near a coal mine industry. Water and sediment samples were taken from three separate locations over two distinct seasons (wet and dry) to compare the seasonal variations of five heavy metals (Cr, Co, Cd, As, and Pb) using inductively coupled plasma mass spectrometry (ICPMS). The average concentrations of the heavy metals under investigation showed a downward sequence of Cr > Pb > Co > As > Cd in both wet and dry seasons. Furthermore, the mean concentration of heavy metals was higher in the Gangetic leaffish (Nandus nandus) than in the striped dwarf catfish (Mystus vittatus) and the ticto barb (Puntius ticto). Additionally, the enrichment factor values of the heavy metals in the sediments were in the following sequence: Cd > Co > Cr > As. The wetland sediment under investigation was not designated as significantly polluted by the pollution load index (PLI < 1). Moreover, the water from these rivers is not fit for human consumption or cooking as the levels of metals tested were higher than what is considered safe. This study highlights the importance of thoroughly evaluating the risks associated with heavy metals in the river. However, the research recommends that relevant authorities implement necessary measures to prevent further contamination, thereby preserving aquatic life in freshwater ecosystems.